2017
DOI: 10.1155/2017/9185934
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathological Changes in the Aorta during Thoracic Aortic Aneurysm Progression on Molecular Level

Abstract: The progression of thoracic aortic aneurysm depends on regulation of aortic wall homeostasis and on changes in the structural components of the extracellular matrix, which are affected by multiple molecular signalling pathways. We decided to correlate the diameter of ascending thoracic aneurysm with gene expression of inflammation markers (IL-6, CRP), cytokine receptors (IL-6R, TNFR1, and TNFR2), and extracellular matrix components (Emilin-1, MMP9, and TIMP) for detection of the degree of pathological process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The clinical value of NLR in unruptured IA, especially in aneurysms smaller than 7 mm, has been found in our study. The increased level of inflammatory cytokines in peripheral blood was associated with aneurysm size in both unruptured IA and thoracic aortic aneurysms ( 29 , 33 ). Larger aneurysm size was more likely to rupture without preventive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical value of NLR in unruptured IA, especially in aneurysms smaller than 7 mm, has been found in our study. The increased level of inflammatory cytokines in peripheral blood was associated with aneurysm size in both unruptured IA and thoracic aortic aneurysms ( 29 , 33 ). Larger aneurysm size was more likely to rupture without preventive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological changes in the aorta in cases of thoracic aortic aneurysm are related to IL-6. 24 IL-6 was involved in the early inflammatory response in patients with AAA. 25 IL-6 gene variants may participate in the development of AAA by regulating IL-6 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that genetic variation in genes associated with extracellular matrix degradation, including MMPs, may contribute to different levels of expression in the aortic wall and the development of aneurysm. Some studies have indicated an increase in the concentrations of MMP1 and MMP9 in the walls of diseased aortas and in plasma in patients with acute thoracic aortic diseases [ 9 , 30 , 31 ]. However, other studies do not support this relationship.…”
Section: Discussionmentioning
confidence: 99%